Inflammatory biomarkers and risk of ischemic stroke and subtypes: A 2-sample Mendelian randomization study. (1st February 2020) - Lin, Jinxi; Wang, Yilong; Wang, Yongjun; Pan, Yuesong
ABSTRACT: Objective: Chronic inflammation is considered as playing an important role in the pathophysiology of atherosclerosis, but the exact contributing inflammatory pathway on stroke is not clear. We aimed to examine the causal association of inflammatory biomarkers, such as interleukin-1 receptor antagonist (IL-1Ra), soluble interleukin-6 receptor (sIL-6R) and C-reactive protein (CRP), with the risk of ischemic stroke and its subtypes. Methods: Two-sample mendelian randomization analyses were performed using IL-1Ra, sIL-6R and CRP related genetic variants as instrumental variables. Summary-level data on ischemic stroke and its subtypes were obtained from the largest GWAS meta-analysis on stroke to date – the Multiancestry Genome-wide Association Study of Stroke (MEGASTROKE) consortium. Associations of IL-1Ra with stroke or its subtypes were estimated using inverse-variance weighted (IVW) method with SNPs rs6743376 and rs1542176 as instruments. Wald ratio method with SNP rs2228145 as the instrument was used for sIL-6R and IVW, MR-Egger, simple and weighted median approaches with 4- or 18-SNPs instruments were used for CRP. Results: Genetically elevated ln(IL-1Ra), ln(sIL-6R) and ln(CRP) levels were not causally associated with ischemic stroke (OR = 1.00, 95% CI: 0.97–1.04, p = 0.80; OR = 0.93, 95% CI: 0.87–0.99, p = 0.03; OR = 1.01, 95% CI: 0.94–1.09, p = 0.78). No significant association was observed between ln(IL-1Ra), ln(sIL-6R) and ln(CRP) level and ischemic stroke subtypes. Conclusions: Our study did not find convincing evidence to support that inflammatory biomarkers like IL-1Ra, sIL-6R and CRP are causally associated with the risk of ischemic stroke or its subtypes.